Evaluation of SMOS Sea Surface Salinity with Argo data along the Exclusive Economic Zone (EEZ) of Pakistan - Muhammad Shafiq; Muhammad Naveed Javed; Adnan Aziz; Mudassar Umar (Egyptian Journal of Remote Sensing and Space Sciences, 2024)
Ocean-Atmosphere interactions have been gradually recognized to play a significant role in hydrological cycle and climate change. It is essential to understand ocean-circulation behaviour, including the Sea Surface Salinity (SSS) which is a root cause of variations in sea water density in both coastal system and open ocean. The study has evaluated the performance of SSS obtained from the Soil Moisture and Ocean Salinity (SMOS) satellite data. Daily Barcelona Expert Center (BEC), SMOS, SSS data from 2012 to 2016 are compared with the salinity observations from Argo floats within the Exclusive Economic Zone (EEZ) of Pakistan. Statistics between a daily reporting Argo float and daily SMOS SSS resulted in a spatial correlation, a bias, a standard deviation, and a variance has been examined to determine the monthly, annual and seasonal variations of SSS. Bias analysis showed the underestimation between −0.52 and −0.008 psu while variance has been observed to be between 0.02 and 0.19 psu. The monthly, seasonal and yearly comparison suggests both SMOS and Argo are are found to be in concurrence. Finally, it has been revealed that SSS retrieval algorithm by BEC SMOS provides good estimation along the EEZ of Pakistan.